Saturday

April 18, 2015

April 18, 2015

Posted by **carmen** on Friday, March 15, 2013 at 10:46pm.

2m^2-m-15=0

using the quadratic formula

2y^2-3y-6=0

- math -
**Reiny**, Friday, March 15, 2013 at 10:55pm2m^2 - m = 15

m^2- (1/2)m = 15/2

m^2 - (1/2)m + 1/16 = 15/2 + 1/16

(m - 1/4)^2 = 121/16

m - 1/4= ± 11/4

m = 1/4 ± 11/4

m = 3 or m = -5/2

the second one is simply subbing into the formula and number-crunching.

let me know what you got.

**Answer this Question**

**Related Questions**